Variety of Qira'at in the Qur'an (Study of Surah Al-Fatihah Qira'at 'Asyrah Shughra and 'Asyrah Kubra) - Sholeh Kamil; Nasution, Muhammad Roihan; Imam Yazid (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2024)
The results of this study are that the differences and varieties of qira'at contained in the Qur'an are not the result of one's ijtihad in determining the type of reading in the Qur'an, but must be based on and based on following the sanad and history that is directly connected to the Prophet Muhammad SAW. because qira'at is a discipline of science that is alone. As for the qira'at asyrah shughra and qira'at asyrah kubra in Surah Al-Fatihah, that there are differences in almost all verses in Surah Al-Fatihah according to qira'at and their respective histories. As for the qira'at asyrah shughra is a qira'at that there are ten imams qurra' and each imam imam qurra' has two narrators, and each of these narrators has one thariq (path) which is commonly called the path of shathibiyyah, so that the total history and path is twenty history and twenty thariq (path). While what is meant by qira'at asyrah kubra is qira'at which is attributed to ten imams qurra' which in each imam qira'at has two narrators, in addition to each History has fifty thariq, so the total is twenty History and a thousand thariq (paths).